2020
DOI: 10.1097/iae.0000000000002840
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography and Optical Coherence Tomography Angiography Parameters in Patients With Phacomatosis

Abstract: Purpose: To compare the retinal vasculature characteristics between eyes of patients with and without phacomatosis. Methods: Case–control observational study with retinal vasculature evaluation by optical coherence tomography and optical coherence tomography angiography of the macula and disk. Results: The study included 80 eyes. Neurofibromatosis Type 1 patients presented with a higher central macular thick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…retinal nerve fiber layer thickness as measured by optical coherence tomography (OCT). First studies have shown that especially OCT has great potential to monitor disease in NF1-related OPGs [ 29 , 30 ], but OCT results were only available for later time points in our cohort, why they were not included in our analysis. Correlation of OCT with imaging findings would be highly relevant and this should be done in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…retinal nerve fiber layer thickness as measured by optical coherence tomography (OCT). First studies have shown that especially OCT has great potential to monitor disease in NF1-related OPGs [ 29 , 30 ], but OCT results were only available for later time points in our cohort, why they were not included in our analysis. Correlation of OCT with imaging findings would be highly relevant and this should be done in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study conducted in patients with different phacomatosis, OCTA assessment of the choriocapillaris and choroid revealed a significantly lower SCP papillary vascular density ( p = 0.048), although no differences were observed in the deep capillary plexus (DCP). 9 This could indicate that impaired vascularization only affects areas corresponding to the choroidal nodules and not the whole retina, making it difficult to detect these changes. Accordingly, we believe that any assessment of the ocular vasculature in patients with choroidal nodules should be qualitative rather than quantitative if large areas are analyzed.…”
Section: Discussionmentioning
confidence: 99%